Evaluation of attributes affecting tenderness differences between Bos taurus and Bos indicus cattle - G. Whipple; M. Koohmaraie; J.D. Crouse; Melvin C. Hunt; R.D. Klemm; Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 1990)
Biological tenderness differences between longissimus muscles from 3/8 and 5/8 Sahiwal (Bos indicus) x Hereford-Angus and from Hereford-Angus (Bos taurus) were evaluated. No significant breed cross effects were observed for carcass traits or rates of pH and temperature decline. Loin steaks from Hereford x Angus had lower (P<.05) shear-force values and higher (P<.05) taste panel tenderness scores at 1 and 14 d postmortem. No breed effects existed for muscle fiber sarcomere length, muscle fiber type, muscle collagen, cathepsin enzyme activity, or calcium-dependent protease-I and -II activity. However, calcium-dependent protease inhibitor activity at 24 hr postmortem was greater (P<.01) in Sahiwal-crosses than for Hereford-Angus. Less protein degradation, which causes tenderization during aging, occurred in Sahiwal-crosses by d 14 than in Hereford-Angus at d 1 postmortem. Therefore, mechanisms involving calcium-dependent protease and its inhibitor may be the principal factors causing tenderness differences between Bos indicus and Bos taurus breeds.
Keywords: Cattlemen& #x27; s Day; 1990; Kansas Agricultural Experiment Station contribution; no. 90-361-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 592; Beef; Tenderness; Bos indicus; Calcium-dependent protease; Inhibitor